Technological readiness and its impact on mobile payment usage: A case study of go-pay. Issue 1 (31st December 2023) - Rahardja, Untung; Hapsari, Intan Dwi; Putra, P.O.HADI; Hidayanto, Achmad Nizar
Abstract: This research was conducted to analyze the factors that influence the use of mobile payment Go-Pay in Indonesia. The modeling of mobile payment usage behavior is a combination of technological readiness theory, technological acceptance theory, valence framework, and usage pattern theory. Data were collected using online questionnaires, which were analyzed using partial least squares-structural equation modeling (PLS-SEM) method. Data analysis of 1, 225 respondents showed that technology readiness influenced significantly positively perceived usefulness, perceived ease of use, and significantly negatively influenced perceived cost and perceived risk. However, out of these four factors, only perceived risk and perceived usefulness that significantly affected the use intention. Furthermore, the results also show that facilitating conditions and use intention significantly and positively affected the usage rate of Go-Pay's basic function, whereas the frequency of usage rate of innovative function of Go-Pay was influenced by facilitating conditions and the frequency of users in using the basic features (usage rate of basic function) of Go-Pay. The results imply that mobile payment companies looking to improve their services might consider optimizing their application to accommodate technology readiness and acceptance factors, as well focus on delivering basic functions well to drive future use of innovative functions.